Nucleophilic Addition of Reactive Dyes on Amidoximated Acrylic Fabrics - Reda M. El-Shishtawy; Manal M. El-Zawahry; Fatma Abdelghaffar; Nahed S. E. Ahmed (The Scientific World Journal)
Seven reactive dyes judiciously selected based on chemical structures and fixation mechanisms were applied at 2% owf of shade on amidoximated acrylic fabrics. Amidoximated acrylic fabric has been obtained by a viable amidoximation process. The dyeability of these fabrics was evaluated with respect to the dye exhaustion, fixation, and colour strength under different conditions of temperature and dyeing time. Nucleophilic addition type reactive dyes show higher colour data compared to nucleophilic substitution ones. FTIR studies further implicate the binding of reactive dyes on these fabrics. A tentative mechanism is proposed to rationalize the high fixation yield obtained using nucleophilic addition type reactive dyes. Also, the levelling and fastness properties were evaluated for all dyes used. Excellent to good fastness and levelling properties were obtained for all samples irrespective of the dye used. The result of investigation offers a new method for a viable reactive dyeing of amidoximated acrylic fabrics.